In vitro and in vivo assessment of caprine origin Staphylococcus aureus ST398 strain UTCVM1 as an osteomyelitis pathogen - Billings, Caroline; Rifkin, Rebecca; Abouelkhair, Mohamed; Jones, Rebekah Duckett; Bow, Austin; Kolape, Jaydeep; Rajeev, Sreekumari; Kania, Stephen; Anderson, David E. (Frontiers in Cellular and Infection Microbiology, 2022)
Staphylococcus aureus (SA) is a significant and well-recognized causative organism of bacterial osteomyelitis. Osteomyelitis is an inflammatory bone disease characterized by progressive bone destruction and loss. This disease causes significant morbidity and mortality to the patient and poses therapeutic challenges for clinicians. To improve the efficacy of therapeutic strategies to combat bacterial osteomyelitis, there is a need to define the molecular epidemiology of bacterial organisms more clearly and further the understanding of the pathogenesis of SA osteomyelitis. We conducted in vitro characterization of the pathogenic capabilities of an isolate of SA ST398 derived from a clinical case of osteomyelitis in a goat. We also report a rodent mandibular defect model to determine the ability of ST398 to cause reproducible osteomyelitis. Our results indicate that ST398 can invade and distort pre-osteoblastic cells in culture, induce significant inflammation and alter expression of osteoregulatory cytokines. We also demonstrate the ability of ST398 to induce osteomyelitis in a rat mandibular model. When compiled, these data support ST398 as a competent osteomyelitis pathogen.